2012
DOI: 10.1186/gb-2012-13-2-r11
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of the maternal-to-zygotic transition in Drosophila primordial germ cells

Abstract: BackgroundDuring the maternal-to-zygotic transition (MZT) vast changes in the embryonic transcriptome are produced by a combination of two processes: elimination of maternally provided mRNAs and synthesis of new transcripts from the zygotic genome. Previous genome-wide analyses of the MZT have been restricted to whole embryos. Here we report the first such analysis for primordial germ cells (PGCs), the progenitors of the germ-line stem cells.ResultsWe purified PGCs from Drosophila embryos, defined their proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 78 publications
3
60
2
1
Order By: Relevance
“…Subcategories represent classification from Figures 2D and 3A. A number of well-characterized RBPs such as Tudor, Piwi, Oskar, Vasa, and Aubergine have been described to exhibit spatial-restricted function in the posterior embryo (Hay et al 1988;Bardsley et al 1993;Breitwieser et al 1996;Harris and Macdonald 2001;Megosh et al 2006). A recent study reported enrichment of 62 proteins in sorted primordial germ cells in early Drosophila embryos (Siddiqui et al 2012). Of these, 18 (29%) proteins were found in the early fly mRBPome (14 known RBPs; four previously unknown: Pp1-87B, CG7920, CG8036, and Mcm7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcategories represent classification from Figures 2D and 3A. A number of well-characterized RBPs such as Tudor, Piwi, Oskar, Vasa, and Aubergine have been described to exhibit spatial-restricted function in the posterior embryo (Hay et al 1988;Bardsley et al 1993;Breitwieser et al 1996;Harris and Macdonald 2001;Megosh et al 2006). A recent study reported enrichment of 62 proteins in sorted primordial germ cells in early Drosophila embryos (Siddiqui et al 2012). Of these, 18 (29%) proteins were found in the early fly mRBPome (14 known RBPs; four previously unknown: Pp1-87B, CG7920, CG8036, and Mcm7).…”
Section: Discussionmentioning
confidence: 99%
“…5A,B; Supplemental Table S4), which differed from TF mRNA localization. Ribosomal proteins have been found to be enriched in primordial germ cells (Siddiqui et al 2012), but mRNAs coding for ribosomal proteins did not contribute to the posterior enrichment observed for RBP transcripts. The observed RBP and TF transcript spatial enrichments were recapitulated for the six previously defined gene expression clusters ( Fig.…”
Section: Embryonic Rbp Transcript Localizationmentioning
confidence: 95%
“…As a consequence, known PGC regulator genes with high maternal protein contribution ( shg , piwi , vas , osk and pum ) were not recovered in our screen. Remarkably, there is no substantial overlap between the maternal transcriptome and proteome [2]. Additional approaches, such as inducible protein degradation techniques, could be applied to deplete maternally provided proteins and analyze their PGC-specific function [40], [41].…”
Section: Discussionmentioning
confidence: 99%
“…Some genomic approaches using FACS-isolated PGCs have directly tested the timing and extent of delays for EGA and maternal transcriptome degradation. Drosophila PGCs do not upregulate embryonically transcribed transcripts until 3 to 5 hours post fertilization, compared to the major somatic EGA, which occurs at 2 hours (Siddiqui et al, 2012). A 1–3 hour delay in Drosophila time is substantial, as this period spans when the PGCs were created, into gastrulation, until just before the PGCs begin migrating to the somatic gonad.…”
Section: Mets Are Delayed In Pgcsmentioning
confidence: 98%
“…Furthermore, the Drosophila PGCs are delayed for degradation of maternal RNA by several hours. At least some mechanistic aspects of EGA and transcript degradation are similar between the germ line and soma, such as the shared requirement for the RNA-binding protein, Smaug (Siddiqui et al, 2012). Similarly, FACS of sea urchin sMics indicated that transcription is inhibited in the sMics from their creation, and they retain inherited mRNA substantially longer than somatic cells (Swartz et al, 2014).…”
Section: Mets Are Delayed In Pgcsmentioning
confidence: 99%